The Multifund System – Is It an Option for Raising the Sustainability of The Bulgarian Pension System? - Jeko Milev; Kremena Choutilova-Yochkolovska (Finance, Accounting and Business Analysis)
Background: Bulgarian universal pension funds have been operating for more than 20 years. They were established into Bulgarian pension system as supplementary elements whose basic aim was to strengthen the sustainability of the system in the long term. Following the recommendations of the World Bank (1994), the policymakers in the country introduced a fully funded defined contribution pension scheme where the investment risk is almost entirely borne by the insured individuals. Hence, low returns realized by pension companies during the accumulation phase detriment seriously the amounts of the pension benefits at the date of retirement. The second pillar pension funds are allowed to structure and manage only one portfolio of assets which could hardly suit the interests of both young and old scheme members. The investment horizon is crucial when it comes to the right mixture of assets in the investment portfolio.